The effect of financial literacy on trust: Do financially literate individuals have more trust in the financial system? - Poher, Beatriz; Núñez Letamendía, Laura (IE University, 2020)
This study analyzes the effect that financial literacy has on individuals’ trust in the financial system. For this end, three different sorts of financial literacy are used, basic financial literacy, financial knowledge of investment products and financial awareness on the role played by financial institutions. Among the three types of financial literacy examined, sophisticated financial literacy, in particular that related to knowledge of investment products, plays the most relevant role in explaining individuals’ financial trust. The findings show that less financially literate individuals are less likely to trust the financial system as a whole, as well as banks. Moreover, individuals with lower financial awareness perceive also lower levels of honesty and solvency in banks.
Keywords: Ahorros; Inversiones; Conocimientos Financieros; Analfabetismo financiero; Sistema financiero; Bancos; Savings; Investments; Financial Knowledge; Financial illiteracy; Financial system; Banking